(untitled) (International Journal of Pharmaceutical Sciences and Drug Research, 2014)
Present study circumspects synthesis of some novel 2-substituted analogues of Benzimidazole and their spectral characterization by means of UV, IR and 1H NMR. The compounds were screened for antibacterial activity against standard strains of both Gram positive and Gram negative bacteria. Results obtained establish compounds KD1 and KD2 to be significantly responsive against different bacterial strains and as such these compounds can pave the way for development of potent antibacterial agents.